Comparison of resin push-out strength to root dentin of bovine- and human-teeth - Galhano, Graziela [UNESP]; Melo, Renata Marques de [UNESP]; Valandro, Luiz Felipe; Bottino, Marco Antonio [UNESP] (Wolters Kluwer, 2009)
Aim : To compare the push-out strength of bovine- and human-root dentin and, thus, evaluate the suitability of bovine-root dentin to substitute human-root dentin for bond strength testing. Materials and Methods : Ten single-rooted human-teeth and ten bovine incisors were prepared using a #3 bur of a fiber post system (12 mm long). The posts were duplicated with resin cement (Duolink). The root canals were treated with All Bond 2 adhesive system and the resin posts were cemented using Duolink. The specimens were cut perpendicular to their long axis, yielding disc-specimens with 1.5 mm thickness, which were submitted to a push-out test (1 mm/min). Ten bond strength values per group (n = 10) were used for statistical analysis (Student t test, a =.05). Results : Statistically significant differences were found for the bond strength values between bovine- (4.1 1.3 MPa) and human-root dentin (8.6 5.7 MPa) (P =.0001). Conclusion : The push-out strengths of bovine- and human-root dentin were statistically different.
Keywords: Bovine tooth; Human-tooth; Push-out test; Root dentin; dentin bonding agent; resin cement; animal; cattle; comparative study; dental bonding; dental care; dental surgery; dentin; disease model; drug effect; endodontics; human; methodology; nonparametric test; standard; tooth crown; tooth root; ultrastructure; Animals; Cattle; Dental Bonding; Dental Marginal Adaptation; Dental Restoration Failure; Dental Stress Analysis; Dentin; Dentin-Bonding Agents; Disease Models, Animal; Humans; Post and Core Technique; Reference Standards; Resin Cements; Root Canal Preparation; Statistics, Nonparametric; Tooth Root